Assessment of Employee Acceptance Towards Learning Management System Used Case Study From PT. Amerta Indah Otsuka (Journal of Business and Management, 2021)
In order to increase employee performance and compete in the fast-growing FMCG business sector, PT Amerta Indah Otsuka needs a learning system called Learning System Management for upskilling and reskilling as well as establishing a growth mindset. To get to the present phenomenon, this research was undertaken first by interviewing PT Amerta Indah Otsuka's Head of Talent Development, and then by administering an online survey questionnaire to employees at the company's head office. The relationship between performance expectancy, effort expectancy and social influence on the behavioral intention to use LMS by employees of PT Amerta Indah Otsuka were the variables that would be evaluated in this study. According to the findings, two independent variables, namely performance expectancy and social influence, influence the behavioral intention of employees of PT Amerta Indah Otsuka to utilize the LMS. In addition, based on the findings, the variable that has a strong influence in influencing behavioral intention is social influence.Keywords : Learning Management System (LMS); PT Amerta Indah Otsuka; Partial Least Square-Structural Equation Model (PLS-SEM); Quantitative; Online Survey